DAMPAK STATUS EKONOMI PADA STATUS GIZI BALITA - Indrawati Aristiyani; mustajab, abdullah azam (Jurnal Keperawatan Widya Gantari Indonesia, 2023)
The nutritional status of toddlers is a health problem that has an impact on children's growth and development. This condition has an impact on the child's physical and mental health in the future. Many factors influence the nutritional status of children under five, one of which is the economic status of the family. The aim of the study was to analyze the relationship between economic status and the nutritional status of toddlers. The research method is cross-sectional by conducting analytic observational, the sample using accidental sampling based on toddlers who carried out anthropometric measurements of toddlers' height and weight obtained 155 toddlers. Analysis of research data with descriptive analysis, chi square analysis and logistic regression test. The results showed that families with low economic status had babies with low birth weight of 21.7%, underweight of 15.2% and stunting of 52.2%. The logistic regression test showed that there was a significant relationship between economic status and low birth weight babies (p value 0.025), underweight (p value 0.023) and stunting (p value 0.008). The conclusion is that there is a significant relationship of family economic status to low birth weight, underweight and stunting.